Utilizing a Qualitative Needs Assessment With Multiple Stakeholders to Design a New Family Medicine Student-Run Clinic - Shanna Tucker; Jana Jarolimova; Nida Naushad; Vidya Viswanathan; Barbara Ogur; Steven R Simon; Monica DeMasi (Journal of Student-Run Clinics, 2019)
Student-faculty clinics have played an important role in caring for underserved populations over the last several decades. In 2013, a multi-site student-faculty primary care practice expanded to a family medicine clinic in Somerville, Massachusetts. A needs assessment was conducted to tailor the design of the new student-faculty clinic to the unmet needs of the patient population. Semi-structured interviews were performed with key stakeholders, including current patients at the health center, clinic staff, and representatives of community organizations. Interviews elucidated such themes as: a desire for lengthened patient visits, interest in more advice on nutrition and weight loss, a need for increased mental health services, and assistance with navigation of the healthcare system. The results of this needs assessment were then incorporated into the design of the new student-faculty clinic, featuring longer appointment times, health education, and close connections to mental health services. This article describes a systematic approach to conducting a comprehensive needs assessment for health professional programs interested in developing student-faculty clinics, and the incorporation of needs assessment results into the design of such a clinic.